Institutional and macroeconomic determinants of financial development in the OIC countries - Abubakar, Abdulsalam; Kassim, Salina (Inderscience Publisher, 2018)
The role of a well-developed and functioning financial system to the growth process of nations is strongly recognized in both the academia and policy cycles. Consequently, the question arose that if financial development is so important to economic growth, then, what determines it is equally worthy of attention. This study is inspired by this concern and the fact that financial development in the OIC member countries is low relative to other developing countries. The study investigated the institutional and macroeconomic determinants of financial development in 50 OIC member countries over the period 2003 to 2011. Due to the potentials of country specific effects and endogeneity of explanatory variables, a dynamic panel approach that is system-GMM was employed. The results revealed that overall level of income positively influences financial development, and exchange rate encourages financial depth and lending activities. Financial openness is found to only promote financial depth, while institutional quality only promotes lending activities. On the other hand, inflation stimulates bank private credit and reduces the depth of the financial sector. This mixed results implied that, policy makers in the OIC countries, shall adopt a hybrid of economic and financial policies as well as implement political, legal and governance reforms in order to strike a balance between the needs of both the suppliers and users of funds, enhance financial development and hence promote economic growth.